2011
DOI: 10.1061/(asce)mt.1943-5533.0000316
|View full text |Cite
|
Sign up to set email alerts
|

Average Crack Spacing of Overlay-Strengthened RC Beams

Abstract: Abstract:The research is focused on evaluating the average crack spacing of overlay-strengthened reinforced concrete (RC) beams. The current equations in different structural codes for predicting the average crack spacing of RC beam with multilayered-reinforcing bars is proved to be inapplicable for overlay-strengthened RC beam, although these two kinds of beams are both with reinforcement in multi-layers. Therefore, a simple, practical and new analytical model that is capable of predicting the average crack s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Decreasing crack spacing was observed with increasing total perimeter steel reinforcements in the overlay at all temperature levels. Zhang et al (2011) observed a similar tendency for PCM overlaid beams tested at room temperature. Based on their study, the average crack spacing increased with increasing tensile strength and effective tensile area of concrete and PCM but decreased with increasing the total perimeter of the tension reinforcements in the overlay and the bond strength of the concrete/steel and PCM/steel interfaces.…”
Section: Effect Of Overlayingsupporting
confidence: 62%
See 1 more Smart Citation
“…Decreasing crack spacing was observed with increasing total perimeter steel reinforcements in the overlay at all temperature levels. Zhang et al (2011) observed a similar tendency for PCM overlaid beams tested at room temperature. Based on their study, the average crack spacing increased with increasing tensile strength and effective tensile area of concrete and PCM but decreased with increasing the total perimeter of the tension reinforcements in the overlay and the bond strength of the concrete/steel and PCM/steel interfaces.…”
Section: Effect Of Overlayingsupporting
confidence: 62%
“…Therefore, it is necessary to predict the cracking behavior of overlaid RC beams. Different structural codes and researchers present models for predicting the crack spacing and width of RC members Zhang et al (2011) concluded that the existing codes are incapable of predicting the crack spacing of overlaid RC beams, and they proposed a new model by considering the equilibrium and compatibility equations between two adjacent cracks and verified the model using a large database. However, the applicability of the proposed model for overlaid beams at elevated temperatures has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Crack spacing depends on the bond between steel and concrete. It was decreased by increasing flexural reinforcement area and more specifically the perimeter of the flexural reinforcement 39‐42 . In this work, flexural reinforcement for all beams was kept constant, whereas the amount of fibers in the concrete was varying, and significant reduction in the crack spacing was observed with the increase in the fibers amount as shown in Figure .…”
Section: Results and Data Discussionmentioning
confidence: 99%
“…It was decreased by increasing flexural reinforcement area and more specifically the perimeter of the flexural reinforcement. [39][40][41][42] In this work, flexural reinforcement for all beams was kept constant, whereas the amount of fibers in the concrete was varying, and significant reduction in the crack spacing was observed with the increase in the fibers amount as shown in Figure 10. Fibers were assumed to strengthen the matrix of concrete and also resist crack propagation with application of load.…”
Section: Crack Spacing and Crack Widthmentioning
confidence: 99%
“…Cracking in strengthened RC structures has a major influence on structural performance, including tensile, bending and shear stiffnesses; energy absorption capacity; ductility; and corrosion resistance of the reinforcement. Moreover, the average crack spacing of strengthened beams plays an important role in the transfer of shear stress along the CFRP laminate-substrate interface with concrete and in the normal stress generated in the concrete substrate in the case when premature debonding failure, such as CFRP peeling or concrete cover separation, is investigated (Zhang et al 2011;Wang and Ling 1998;Raoof and Hassanen 2000).…”
Section: Introductionmentioning
confidence: 99%